Evaluation of DNA barcodes in discriminating Quercus species from Lam Dong, Vietnam - Van Ngoc, Nguyen; Van Duy, Nong; Minh Phuong, Nguyen Thi; Binh, Hoang Thi (Vietnam Journal of Biotechnology, 2022)
DNA barcoding is a tool for species discrimination and identification which helps overcome the problem of identification that cannot be covered by morphological identification. Quercus is the second biggest genus of Fagaceae in Vietnam as well as Lam Dong province after Lithocarpus. However, the species discrimination study of the Quercus species in Vietnam and Lam Dong province has yet to be well uncovered due to ambiguous species boundaries and the lack of universal molecular markers. In this study, the DNA barcodes were tested to discriminate among the species of the Quercus genus in Lam Dong province. A total of sixteen and two samples of the Quercus and Lithocarpus genus (out-group) were tested using matK, rbcL, and internal transcribed spacer (ITS). Of which, the new sequences in this study were sequenced from six species and one unknown species of Quercus, the rest was retrieved from GenBank. The BLAST, neighbor-joining, and Bayesian methods were employed to examine species discrimination success. The results showed that ITS was an efficient single-locus barcode for Quercus species by yielding the highest rate of universality as well as the best discriminatory and authentication power among the barcodes examined. In addition, the combination of ITS+matK+rbcL achieved the highest species discrimination. Therefore, matK and rbcL should not be used as DNA barcodes for the species identification of Quercus, whereas the combination of three genes that were proposed in this study is the most suitable DNA barcode for identifying Quercus species in Lam Dong province.